Evidence of User-Expert Gaps in Health App Ratings and Implications for Practice - de Chantal, Pier-Luc; Chagnon, Alexandre; Cardinal, Michael; Faieta, Julie; Guertin, Alexandre (Frontiers in Digital Health, 2022)
Searching the commercial Google Play Store and App Store is one of the most common strategies for discovering mobile applications for digital health, both among consumers and healthcare professionals. However, several studies have suggested a possible mismatch between this strategy and the objective of finding apps in physical and mental health that are both clinically relevant and reliable from a privacy standpoint. This study provides direct evidence of a gap between the five-star user rating system and expert ratings from a curated library of over 1,200 apps that cover both physical and mental health. An objective metric is derived to assess the strength of the user-expert gap for each app, which in turn allows identifying missed opportunities—low user ratings and high expert ratings—and overrated apps—high user ratings and low expert ratings. Implications for practice and care delivery are discussed.